A Feminist Ventriloquial Analysis of Hao Gongzuo ("Good Work"): Politicizing Chinese Post-1980s Women's Meanings of Work. Issue 4 (1st October 2016) - Long, Ziyu
ABSTRACT: This study examines Chinese post-1980s women's meanings of work at the intersections of gender, generation, and culture. A feminist ventriloquial approach is used to tease out the enactment of tensions in the communicative constitutions of the colloquialism hao gongzuo ("good work"). Figures such as women's personal aspirations, gender roles, cultural and generational values, and the material conditions of the Chinese workplace ventriloquize into their everyday constructions. This study finds that post-1980s women are both perpetuators and dissidents of gendered and national-cultural work ideology as they negotiate various tensions to frame good work as wending (stable), timian (face adding, status promoting), and yourenyouyu (fulfilling, achieving). Situated in the context of a transitional developing country rooted in Eastern traditions, this study unpacks how various discursive and material forces engage in tensional constructions of work meanings and sheds light on women's career socialization and gender equity in the Chinese workplace.